Ophthalmopathy in childhood Graves' disease. Issue 7 (1st July 2002) - Chan, W; Wong, G W K; Fan, D S P; Cheng, A C K; Lam, D S C; Ng, J S K
Abstract : Aims: To study the ocular manifestations and their severity in children with Graves' disease. Methods: All patients with Graves' disease having regular follow up in a paediatric endocrine clinic were recruited for the study. A comprehensive ophthalmic assessment including ocular motility, exophthalmometry, intraocular pressure (IOP), slit lamp, and fundus examinations was performed. Results: 83 patients (72 female, 11 male) aged 16 years or below were examined. All are Chinese. Ocular symptoms occurred in 12 patients. Ocular signs of ophthalmopathy were documented in 52 patients (62.7%). Most of them presented with eyelid abnormalities such as lid oedema, lid lag, and lagophthalmos, whereas lower lid retraction was the commonest clinical sign noted (38.6%). Diffuse conjunctival injection was found in four patients (4.8%). 10 patients (12.0%) had mild proptosis of less than 3 mm. Only one patient (1.2%) had limited extraocular motility in extreme gaze. Punctate epithelial corneal erosions were reported in 11 patients (13.3%). Conclusions: This is the largest series on the ocular complications of childhood Graves' disease in the literature. Although 52 patients (62.7%) were identified with positive ocular changes, none of them had visual threatening complications or debilitating myopathy.